ANALISIS SISTEM INFORMASI PENGADUAN MASYARAKAT BERBASIS WEB PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL - gabriel aldosion; Dimas Saputra (PT Jurnal Cendekia Indonesia, 2025)
The advancement of information technology has prompted governmental agencies to integrate digital solutions, such as the Civil Registry Service (Dukcapil). This research focuses on an online public complaint information system designed to enhance the effectiveness of public services. The approach taken is qualitative, utilizing observation, interviews, and UML modeling techniques. Findings indicate that the current manual system suffers from notable drawbacks, including sluggish responses and insufficient transparency. The online system, created with PHP and MySQL and evaluated via Black Box Testing, has demonstrated success in addressing these issues. This research intends to serve as a guide for the creation of comparable systems in other government agencies.